Personal Competition Among Sports Players and Their Performance as a Team: A Moderated Mediation Model - Li, Jinling (Frontiers in Psychology, 2022)
Personal competition among the colleagues and co-workers has been observed in order to prove their professional superiority over others. Such behaviors have grave consequences on the overall team performance. The aim of the present study was to investigate the role of personal competition on the team performance incorporating the mediating role of playing dumb behavior of knowledge hiding. The study has further checked the moderating effect of task interdependence on the relationship between personal competition and playing dumb. Data for the present study had been collected through questionnaires from the sports players actively associated with games through their educational institutes in China. The sample size of the study was 339 selected on the basis of convenience sampling. Smart PLS had been employed to analyze the data through structural equation modeling (SEM). The results of the study showed a strong impact of personal competition on team performance and the playing dumb variable. Furthermore, playing dumb has been found to have strong mediating impact on the team performance. The study has theoretically contributed in the literature of competition and performance by investigating the mediating role of playing dumb. The study also offers certain practical implications to the managers of the corporate world to devise such human resource policies that take appraisals from the colleagues so to rectify the negative workplace behaviors and could be worked out accordingly.